Analysis of the binding selectivity and inhibiting mechanism of chlorogenic acid isomers and their interaction with grass carp endogenous lipase using multi-spectroscopic, inhibition kinetics and modeling methods. (15th July 2022) - Xu, Zeru; Cao, Qiongju; Manyande, Anne; Xiong, Shanbai; Du, Hongying
Highlights: NCGA and CCGA can form a compact complex with grass carp lipase. CGA isomers quenched the fluorescence of lipase by static quenching. The major driving forces are different in CGA isomers bound to lipase. Neochlorogenic acid (NCGA) has stronger inhibitory effects on lipase. Abstract: Polyphenols are inhibitors for lipase, but the binding selectivity and mechanism of polyphenol isomers and how they interact with lipase are not clear. Here, chlorogenic acid (CGA) isomers, neochlorogenic acid (NCGA) and cryptochlorogenic acid (CCGA) were used to explore the binding selectivity and mechanism of lipase. An inhibition assay indicated that both CGA isomers had dose-dependent inhibitory effects on lipase; however, the inhibitory effect of NCGA was better (IC50 : 0.647 mg/mL) than that of CCGA (IC50 : 0.677 mg/mL). NCGA and CCGA formed complexes with lipase at a molar ratio of 1:1, and the electrostatic interaction force plays a major role in the lipase–CCGA system. Molecular dynamics studies demonstrated that NCGA had a greater impact on the structure of lipase. The multi-spectroscopic and modeling results explained the effects of micro-structural changes on the binding site, the interaction force and the inhibition rate of the isomers when they combined with lipase.